Pengaruh Kualitas Pelayanan dan Promosi Terhadap Volume Penjualan Pada Konsumen di Dunkin Donuts Cabang Kesawan - Ervina Sari Ramadhan; Tika Nirmala Sari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of service quality and promotion on consumer sales volume at Dunkin' Donuts Kesawan Branch. This study employed quantitative research. The data sources used were primary and secondary data. Data collection techniques included questionnaires, interviews, and documentation. Data analysis techniques used were descriptive statistics, classical assumption tests, multiple linear regression tests, and hypothesis testing. The sample size for this study was 100 respondents. The partial test results revealed that service quality had a positive and significant effect on sales volume at Dunkin' Donuts Kesawan Branch, with a t-value of 3.844 > 1.984. The promotion variable has a positive and significant effect on sales volume at Dunkin' Donuts Kesawan Branch, with a calculated t-value of 2.215 > 1.984. The simultaneous test results show that the calculated f-value > f-table, i.e., 8.087 > 3.09. Therefore, it can be concluded that the service quality (X1) and promotion (X2) variables jointly have a positive and significant effect on sales volume at Dunkin' Donuts Kesawan Branch.